A Pilot Study Using Preoperative Cerebral Tissue Oxygen Saturation to Stratify Cardiovascular Risk in Major Non-Cardiac Surgery. Issue 2 (March 2017) - Wen, S. Y. B.; Peng, A. Z. Y.; Boyle, S.; Cai, S.; Pope, L.; Tran, M. T.; Short, T. G.; Aneman, A.; Jaeger, M.; Chuan, A.
This prospective pilot study evaluated whether low preoperative cerebral tissue oxygen saturation is associated with unfavourable outcomes after major elective non-cardiac surgery. Eighty-one patients over 60 years of age, American Society of Anesthesiologists physical status 3 or 4, were recruited. Resting cerebral tissue oxygen saturation was recorded on room air, and after oxygen supplementation, using cerebral oximetry. The primary outcome was 30-day major adverse event of combined mortality or severe morbidity, and the secondary outcome was 30-day new disability. Eleven patients (13.6%) suffered a major adverse event, and 28 patients (34.6%) experienced new disability. Room air cerebral tissue oxygen saturation was significantly different between patients who had a major adverse event, 67% (95% confidence interval [CI] 65–70) versus unaffected, 71% (95% CI 70–72; P=0.04). No statistical difference was found between patients for new disability (range 70%– 74%; P=0.73). Room air cerebral tissue oxygen saturation was significantly associated with major adverse events (odds ratio 1.36 (95% CI 1.03–1.79), P=0.03). Saturation levels ≤68% carried a positive likelihood ratio of 2.2 for death or severe morbidity, P=0.04. A definitive trial is required to confirm if cerebral oximetry can be used to stratify the cardiovascular risk of patients presenting for non-cardiac surgery.